Strategi Pemerintah Daerah Dalam Penanggulangan Stunting (Studi Di Wilayah Kecamatan Sukadiri Kabupaten Tangerang) - Songgot, Reonald; Ginola, David; Fachry Tegar, Yudistira; Khikmawatanto, Khikmawatanto (CV RIFAINSTITUT, 2023)
Based on data from the 2022 National Nutrition Status Survey (SSGI), the prevalence of stunting in Indonesia is 21.6%, where the national target for stunting prevalence in 2024 is 14%, so this study aims to observe the role of the Regional Government, especially the Regional Government of Tangerang Regency to overcome one of the national issues is child growth and development disorders or stunting that occurs in the Pantura region of Tangerang Regency. This research method uses qualitative research based on library research which consists of recording all findings regarding the research problem and behavior observations both verbally and in writing to produce descriptive data. The findings in this study can be concluded that the role of the Regional Government of Tangerang Regency in succeeding in what has become the Government's National Strategy has been going according to plan, as evidenced by the reduction in stunting rates issued by the Tangerang District Health Office in 2022 of 9,200 cases where there is a decrease in stunting rates from in 2021 there will be 16,100 cases.